Anti-aging sole material and preparation method thereof

By combining modified centrosite with EPDM rubber and other materials in sole materials, the aging problem of existing sole materials is solved, and efficient anti-thermal oxygen and anti-UV aging effects are achieved, extending service life and improving The durability of the material.

CN119176990AInactive Publication Date: 2024-12-24含山县嘉裕新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411261782.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During use, existing sole materials are prone to aging due to heat, oxygen, light and other factors, resulting in a decrease in tensile strength, cracks and fractures, and shorten their service life.

Method used

Modified actolite is combined with ethylene propylene tereum rubber, acrylate rubber and other materials. Through the synergistic effect of the modified actolite and the anti-aging structure of amines, it enhances the anti-oxidation and ultraviolet rays and improves the heat resistance of the material. Oxygen and anti-UV aging properties.

Benefits of technology

It significantly extends the service life of the sole material, improves its anti-thermal oxygen and UV aging properties, prevents cracking, powdering or hardening, and improves the comfort and durability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005035907410000021
    Figure BDA0005035907410000021
  • Figure BDA0005035907410000022
    Figure BDA0005035907410000022
  • Figure BDA0005035907410000031
    Figure BDA0005035907410000031
Patent Text Reader

Abstract

The invention discloses an anti-aging sole material and a preparation method thereof, and belongs to the technical field of high polymer materials. The anti-aging sole material is prepared from the following raw materials in parts by weight: 50 to 60 parts of ethylene propylene diene monomer, 10 to 20 parts of acrylate rubber, 6 to 12 parts of modified rectorite, 1 to 1.5 parts of sorbitan oleate, 1 to 2 parts of vulcanizing agent, 0.5 to 0.8 part of vulcanization accelerator, 1 to 3 parts of lubricant and 0.5 to 0.8 part of cross-linking agent. The modified rectorite has good compatibility with other raw materials in the sole material, and the modified rectorite can be highly dispersed and stably exist in the sole material, so that the rectorite, the hindered phenol structure and the amine anti-aging component in the modified rectorite have a synergistic effect; the materials jointly enable the sole material to have efficient and lasting thermo-oxidative aging resistance and ultraviolet aging resistance, and the service life of the sole material is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an anti-aging sole material and a preparation method thereof. Background Art

[0002] The sole material is a byproduct of footwear products. With the development of footwear products, the quality of sole materials has been continuously improved. Modern soles are mostly made of artificial materials, mainly synthetic rubber, plastic, etc. The aging problem of rubber products has always attracted much attention. The aging of rubber mainly refers to the phenomenon that rubber products undergo physical and chemical changes during storage or use due to the influence of external factors such as heat, oxygen, light, mechanical stress, ozone, harmful metal ions, chemical media, etc., and then the rubber performance deteriorates and gradually loses its use value. Aging is a process in which the performance of a material changes from good to bad. At present, the sole materials on the market have a significant decline in aging resistance after being used for a period of time, which directly affects their tensile strength, is more prone to cracks or even breaks, and greatly shortens their service life. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the prior art and provide an anti-aging sole material and a preparation method thereof.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] An anti-aging sole material comprises the following raw materials in parts by weight:

[0006] 50-60 parts of EPDM rubber, 10-20 parts of acrylate rubber, 6-12 parts of modified rectorite, 1-1.5 parts of sorbitan oleate, 1-2 parts of vulcanizing agent, 0.5-0.8 parts of vulcanization accelerator, 1-3 parts of lubricant, and 0.5-0.8 parts of crosslinking agent.

[0007] Further, the modified rectorite is prepared by the following steps:

[0008] S1. Add p-phenylenediamine, triethylamine and chloroform to a dry three-necked flask under nitrogen protection, stir until completely dissolved, then slowly add a mixed solution of 4-bromo-2,6-di-tert-butylphenol and chloroform, and after the addition is complete, place the flask in a 0°C ice-water bath and stir to react for 6 hours. After the reaction is completed, perform vacuum distillation, column chromatography purification (the eluent is a mixed solvent of benzene and acetone, and the volume ratio of benzene and acetone is 9:1), and vacuum distillation to obtain intermediate 1; the amount ratio of p-phenylenediamine, 4-bromo-2,6-di-tert-butylphenol, triethylamine and chloroform is 0.095 mol:0.09 mol:15 mL:180 mL;

[0009] Triethylamine is used as an acid-binding agent to react the -NH2 of p-phenylenediamine with the -Br of 4-bromo-2,6-di-tert-butylphenol to form a nucleophilic substitution reaction. The reaction process is shown below:

[0010]

[0011] S2. Add intermediate 1 and DMSO (dimethyl sulfoxide) to a dry three-necked flask under nitrogen protection, stir evenly and then slowly add a mixed solution of maleic anhydride and DMSO. After the addition is complete, heat to 40°C and stir to react for 1 hour. After the reaction is completed, perform vacuum distillation, column chromatography purification (the eluent is a mixed solvent of chloroform and ether, and the volume ratio of chloroform to ether is 9:1), and vacuum distillation to obtain intermediate 2; the amount ratio of intermediate 1, maleic anhydride and DMSO is 0.08 mol:0.084 mol:180 mL;

[0012] The amino group on intermediate 1 attacks the carbonyl carbon ion on maleic anhydride, the anhydride carbon-oxygen bond breaks, and the hydrogen on the amino group leaves in the form of a proton and combines with the oxygen anion. The reaction process is as follows:

[0013]

[0014] S3. Under nitrogen protection, add rectorite to a three-necked flask containing DMSO, ultrasonically disperse for 15 minutes, then slowly add the mixed solution of intermediate 2 and DMSO under stirring, slowly add concentrated sulfuric acid after the addition is completed, heat to 100°C, stir and react for 1 hour, filter after the reaction is completed, wash with deionized water until the filtrate is neutral, and then place it at 100°C for vacuum drying for 6 hours to obtain modified rectorite. The amount ratio of rectorite, intermediate 2, concentrated sulfuric acid and DMSO is 9g:4g:0.52mL:100mL.

[0015] There are abundant hydroxyl groups on the surface of rectorite. Under acidic conditions, the carboxyl group of intermediate 2 and the hydroxyl groups on the surface of rectorite undergo esterification reaction. The reaction process is as follows:

[0016]

[0017] Modified rectorite contains rectorite, which has high temperature stability and adsorption properties. At the same time, rectorite naturally has good ultraviolet blocking ability and has a significant effect in absorbing and blocking short-wavelength light or rays. Therefore, adding modified rectorite to the sole material can absorb odor and effectively block ultraviolet rays to prevent aging and cracking of the sole material.

[0018] Modified rectorite contains hindered phenol structure and amine anti-aging structure. The hindered phenol structure has excellent antioxidant ability. Since the hydroxyl group of the hindered phenol structure is restricted by spatial obstacles, the hydrogen atom can easily fall off from the original molecular structure, thereby achieving the effect of donating protons and combining with peroxyl radicals, alkyl radicals, hydroxyl radicals, etc., causing them to lose their original activity, resulting in the termination of the oxygen aging reaction; the amine anti-aging structure achieves light protection by capturing free radicals, decomposing hydroperoxides, quenching singlet oxygen and capturing heavy metal ions. The amine anti-aging structure has high light stabilization efficiency. Therefore, adding modified rectorite to the sole material can effectively prevent the sole material from cracking, powdering or hardening due to thermal oxygen aging, affecting the comfort and service life of the shoes.

[0019] The modified rectorite contains lipophilic ester groups and benzene rings, which greatly increase the compatibility between the modified rectorite and other raw materials, so that the modified rectorite can be uniformly dispersed in the sole material. In addition, the modified rectorite contains carbon-carbon double bonds, which can produce chemical reactions with the carbon-carbon double bonds of the EPDM side chain under the action of a cross-linking agent, which greatly increases the dispersion of the improved rectorite and enables it to stably exist in the sole material, fully play its role and absorb odors. At the same time, the rectorite works synergistically with hindered phenol structures and amine anti-aging ingredients, which together make the sole material have efficient and lasting resistance to thermal oxidation aging and ultraviolet aging, greatly increasing the service life of the sole material.

[0020] Furthermore, the vulcanizing agent is a mixture of N,N'-dicinnamyl-1,6-hexanediamine and trithiocyanuric acid in a mass ratio of 2:1.

[0021] Furthermore, the vulcanization accelerator is N-cyclohexyl-2-benzothiazole sulfenamide.

[0022] Furthermore, the lubricant is one or more of stearic acid, zinc stearate, paraffin, polyethylene wax, and ethylene bisstearamide.

[0023] Furthermore, the cross-linking agent is one or more of di-tert-butyl peroxide, dibenzoyl peroxide, and diisopropylbenzene peroxide.

[0024] A method for preparing an anti-aging sole material comprises the following steps:

[0025] The raw materials are weighed according to weight and mixed evenly, and then sent into a twin-screw extruder for extrusion granulation and plasticization molding to prepare the sole material.

[0026] Beneficial effects of the present invention: the modified rectorite of the present invention has good compatibility with other raw materials in the sole material, and the modified rectorite can be highly dispersed and stably present in the sole material. Therefore, the rectorite, hindered phenol structure and amine anti-aging components in the modified rectorite work synergistically, and together make the sole material have efficient and lasting anti-thermal oxygen aging effect and anti-ultraviolet aging effect, which greatly increases the service life of the sole material. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] The modified rectorite is prepared in the following specific steps:

[0030] S1. Under nitrogen protection, 10.3 g of p-phenylenediamine, 15 mL of triethylamine and 80 mL of chloroform were added to a 500 mL dry three-necked flask, and stirred until completely dissolved. Then, a mixed solution of 25.7 g of 4-bromo-2,6-di-tert-butylphenol and 100 mL of chloroform was slowly added. After the addition was completed, the flask was placed in a 0°C ice-water bath and stirred for reaction for 6 hours. After the reaction was completed, it was distilled under reduced pressure, purified by column chromatography (the eluent was a mixed solvent of benzene and acetone, and the volume ratio of benzene and acetone was 9:1), and distilled under reduced pressure to obtain intermediate 1;

[0031] S2. Under nitrogen protection, 25 g of intermediate 1 and 140 mL of DMSO were added to a 500 mL dry three-necked flask. After stirring, a mixed solution of 8.2 g of maleic anhydride and 40 mL of DMSO was slowly added. After the addition was completed, the temperature was raised to 40° C. and stirred for 1 h. After the reaction was completed, the mixture was distilled under reduced pressure, purified by column chromatography (the eluent was a mixed solvent of chloroform and ether, and the volume ratio of chloroform and ether was 9:1), and distilled under reduced pressure to obtain intermediate 2.

[0032] S3. Under nitrogen protection, add 9 g of rectorite into a 250 mL three-necked flask containing 90 mL of DMSO, and disperse it ultrasonically for 15 min. Then, slowly add a mixed solution of 4 g of intermediate 2 and 10 mL of DMSO under stirring. After the addition is completed, slowly add 0.52 mL of concentrated sulfuric acid, heat to 100 ° C, stir and react for 1 h. After the reaction is completed, filter and wash with deionized water until the filtrate is neutral. Then place it at 100 ° C and vacuum dry for 6 h to obtain modified rectorite.

[0033] Example 2

[0034] Prepare the sole material, the specific steps are as follows:

[0035] The raw materials are weighed by weight and 50 parts of ethylene propylene diene monomer rubber, 10 parts of acrylic rubber, 6 parts of modified rectorite, 1 part of sorbitan oleate, 0.7 parts of N,N'-secinnamyl-1,6-hexanediamine, 0.3 parts of trithiocyanuric acid, 0.5 parts of N-cyclohexyl-2-benzothiazole sulfonamide, 1 part of stearic acid and 0.5 parts of diisopropylbenzene peroxide are mixed evenly, and then sent into a twin-screw extruder for extrusion granulation and plastic molding to prepare a sole material.

[0036] Example 3

[0037] Prepare the sole material, the specific steps are as follows:

[0038] The raw materials are weighed by weight and 58 parts of ethylene propylene diene monomer rubber, 18 parts of acrylic rubber, 10 parts of modified rectorite, 1.2 parts of sorbitan oleate, 1 part of N,N'-secinnamyl-1,6-hexanediamine, 0.5 parts of trithiocyanate, 0.6 parts of N-cyclohexyl-2-benzothiazole sulfonamide, 2 parts of zinc stearate and 0.6 parts of dibenzoyl peroxide are mixed evenly, and then sent into a twin-screw extruder for extrusion granulation and plastic molding to prepare a sole material.

[0039] Example 4

[0040] Prepare the sole material, the specific steps are as follows:

[0041] The raw materials are weighed according to weight, and 60 parts of ethylene propylene diene monomer rubber, 20 parts of acrylic rubber, 12 parts of modified rectorite, 1.5 parts of sorbitan oleate, 1.3 parts of N,N'-secinnamyl-1,6-hexanediamine, 0.7 parts of thiocyanuric acid, 0.8 parts of N-cyclohexyl-2-benzothiazole sulfonamide, 1.5 parts of ethylene bisstearamide, 1.5 parts of polyethylene wax, and 0.8 parts of di-tert-butyl peroxide are mixed evenly, and then sent into a twin-screw extruder for extrusion granulation, and plasticized and molded to prepare a sole material.

[0042] Comparative Example 1

[0043] Prepare the sole material, the specific steps are as follows:

[0044] The remaining steps remain unchanged, only the modified rectorite in Example 4 is replaced by rectorite without any treatment to prepare the sole material.

[0045] Comparative Example 2

[0046] Prepare the sole material, the specific steps are as follows:

[0047] The remaining steps remained unchanged, except that the modified rectorite in Example 4 was replaced by 8.3 parts of untreated rectorite, 1.85 parts of antioxidant 1010 and 1.85 parts of diphenylamine to prepare the sole material.

[0048] Performance Testing

[0049] The sole materials prepared in Examples 2-4 and Comparative Examples 1-2 were aged at 100° C. for 48 h, and in an ultraviolet lamp aging test box with a UVA-340 light source, 0.83 W﹒ m -2 nm -1 Radiation energy, aging at 70℃ for 20h, testing the tensile strength and elongation at break of the sole material before and after thermal aging and UV aging. The test results are shown in Table 1 below:

[0050] Table 1

[0051]

[0052]

[0053] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0054] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An anti-aging sole material, characterized in that: The composition comprises the following raw materials in parts by weight: 50-60 parts of EPDM rubber, 10-20 parts of acrylate rubber, 6-12 parts of modified rectorite, 1-1.5 parts of sorbitan oleate, 1-2 parts of vulcanizing agent, 0.5-0.8 parts of vulcanization accelerator, 1-3 parts of lubricant, and 0.5-0.8 parts of crosslinking agent; Wherein, the modified rectorite is prepared by the following steps: S1. Add p-phenylenediamine, triethylamine and chloroform into a flask under nitrogen protection, stir, add 4-bromo-2,6-di-tert-butylphenol and chloroform, react at 0°C for 6h, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 1; S2. Add intermediate 1 and DMSO into a flask under nitrogen protection, add maleic anhydride and DMSO after stirring, react at 40° C. for 1 h, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 2; S3. Under nitrogen protection, add rectorite into a flask containing DMSO, disperse by ultrasonication, add intermediate 2, DMSO and concentrated sulfuric acid, react at 100° C. for 1 h, filter, wash and dry to obtain modified rectorite.

2. The anti-aging sole material according to claim 1, characterized in that: The amount ratio of p-phenylenediamine, 4-bromo-2,6-di-tert-butylphenol, triethylamine and chloroform in step S1 is 0.095 mol: 0.09 mol: 15 mL: 180 mL.

3. The anti-aging sole material according to claim 1, characterized in that: The usage ratio of intermediate 1, maleic anhydride and DMSO in step S2 is 0.08 mol:0.084 mol:180 mL.

4. The anti-aging sole material according to claim 1, characterized in that: The usage ratio of rectorite, intermediate 2, concentrated sulfuric acid and DMSO in step S3 is 9g:4g:0.52mL:100mL.

5. The anti-aging sole material according to claim 1, characterized in that: The vulcanizing agent is a mixture of N,N'-dicinnamyl-1,6-hexanediamine and trithiocyanate in a mass ratio of 2:

1.

6. The anti-aging sole material according to claim 1, characterized in that: The vulcanization accelerator is N-cyclohexyl-2-benzothiazole sulfenamide.

7. The anti-aging sole material according to claim 1, characterized in that: The lubricant is one or more of stearic acid, zinc stearate, paraffin, polyethylene wax, and ethylene bisstearamide.

8. The anti-aging sole material according to claim 1, characterized in that: The cross-linking agent is one or more of di-tert-butyl peroxide, dibenzoyl peroxide, and dicumyl peroxide.

9. The method for preparing an anti-aging sole material according to claim 1, characterized in that: The steps include: The raw materials are weighed according to weight and mixed evenly, and then sent into a twin-screw extruder for extrusion granulation and plasticization molding to prepare the sole material.